Credit Risk and Profitability Position of Nepalese Private and Joint Venture Commercial Banks (The Batuk, 2023)
Credit concentrations, credit processes and other externalities have made credit risk more important over the past decade, followed by liquidity issues. This study was conducted to compare the credit risk exposure of various banks in terms of their liquidity, capital ratio, size, operational inefficiency, loan growth rate, and non-performing loans. It also investigated the spontaneous relationship between credit risk and bank profitability. Secondary data of 5 years from ten banks (5 each from joint venture and private banks) have been collected.  The descriptive and comparative study designs were employed and SPSS software was used for the analysis of data. The results showed that the private banks surpass joint venture banks in terms of capital ratio and operating efficiency, but joint venture banks lead private banks in terms of liquidity, capital ratio, total assets, loan growth rate, and non-performing loans. However, the independent sample t-test did not show any significant differences on liquidity, capital ratio, size, and loan growth rate. The Pearson’s correlation showed positive associations of capital ratio (moderate and significant), operating inefficiency (weak and insignificant), and loan growth rate (weak and insignificant) with ROA. In contrast, bank size and nonperforming loans have significant moderate negative correlations, but liquidity is not found to be correlated with ROA. The empirical findings of this study are considered helpful in evaluating the comparative credit risk exposure of the banking sector and have both managerial and academic implications.